Towards circular food production systems: Identification of chemical, microbial, and physical food safety hazards in municipal sludge and excess aerobic biomass of the food industry - Katja C.W. van Dongen; Gijs W. Spaans; Edwin M. Foekema; Johan W. van Groenestijn; A. Maarten J. Kootstra; Michael S.M. Brouwer; Dirkjan Schokker; Paul B. Stege; Bas van Dijk; René A.M. Dirks; Denise van de Kamer; Ruben Kause; et al. (Environment International, 2025)
There is a need in Europe to re-use residual streams to move towards a more circular food production system in the future. Sludge from both municipal wastewater (sewage) treatment plants and from wastewater treatment plants of the food industry (i.e., aerobic biomass) are present in large volumes, contain nutrients, and are currently mostly incinerated in the Netherlands. This makes them an interesting source for re-use in food production systems. However, prior to re-use of these streams in a food production system, the presence of hazardous substances (chemicals, microbiological, and physical) needs to be evaluated to safeguard food safety of such systems. This study aims to evaluate this in sewage sludge collected from multiple locations and in excess aerobic biomass from food industry plants, sampled at 2 – 4 time points. Hazards were analyzed in all samples and included pathogenic bacteria, microbial composition, antimicrobial resistance (genes), viruses, heavy metals, pharmaceutical and pesticide residues, short-chain per- and polyfluoroalkyl substances, dioxins, and physical hazards. Generally, aerobic biomass from wastewater treatment plants of the food industry contained less of the above-mentioned hazards as compared to sludge from municipal wastewater treatment plants. When available, hazard concentrations were compared with maximum limits for fertilizer applications. For heavy metals, these limits were especially exceeded by found cadmium concentrations. Overall, the results of the present study will contribute to the design of safe circular food production systems and showcase the need for a fit-for-purpose and safe-by-design approach in the application of residual streams in food production systems.